AB0286 Biological drugs in chronic inflammatory arthropathies: discontinuation rate of first anti-tnf treatment. (23rd January 2014) - Pietrosanti, M.; Di Rosa, R.; Salemi, S.; Markovic, M.; Catoni, M.; Fantò, M.; Laganà, B.; Sorgi, M. L.; D'Amelio, R.
Abstract : Background: Anti-TNF drugs revolutioned inflammatory arthropathies treatment, cutting down their clinical evolution and giving rise to remarkable benefits in patients life quality. Objectives: It has been carried out a retrospective study to evaluate the correlations with demographic data and clinical parameters in patients suffering of arthritis rheumatoid (RA) or psoriatic arthritis (PsA) in case of interruption of the first anti-TNF drug treatment. Methods: From November 2004 to October 2011, 239 patients affected by RA (n=165), PsA (n=74) have been recruited for first anti-TNF drug treatment For every patient have been weighed: age, sex, pre-therapy illness activity, evaluated by DAS44, selected anti-TNF drug (infliximab, etanercept, adalimumab), interruptions of the treatment and their causes, divided in adverse events, inefficacy, and other ones (pregnancy, poor compliance, surgical operations etc.). The patients that did not interrupt the treatment have been defined as Responder and those who stop it or who make a switch as Non Responder. A statistical assessment about the possible correlation between Responder/Non Responder condition, different drugs used and demographic and clinical parameters was made by Chi-Quadro and T-Student tests. Results: 110 of the 239 patients (46%) stopped the treatment with the first anti-TNF drug: 45% (n=74) patients with RA, 49% (n=36) with PsA. Statistically significant differences are not recorded among global rate of patients who interrupt etanercept (56% n=63), infliximab 50% (n=17) and adalimumab 50% (n=30). A more detailed analysis among the stopping reasons found adverse events in the 22% of the cases (n=52), ineffectiveness in 13% (n=32), and other causes in 9.2% (n=26). Infliximab showed the onset of adverse events in 38% of cases (13 pts) in comparison to 19% (28 pts) for etanercept and to 18% (11 pts) for adalimumab. Etanercept appears to be associated with a statistically significant lower occurrence of discontinuation for adverse events, compared to infliximab (p<0.03). Comparing to same factor adalimumab vs infliximab we obtain a correlation near to statistical significance (p<0.054). Among the analyzed demographic and clinical parameters, pre-treatment disease activity showed a statistical correlation with first anti-TNF interruption: Non Responder patients with RA e PsA presented a higher value of DAS respect to the Responder ones (p<0.005); the group of the Non Responder patients showed a longer duration of illness respect the group of Responder patients (p<0.052). Conclusions: Infliximab is associated to higher discontinuation rate for adverse events, in comparison with etanercept and adalimumab. Among evaluated demographic and clinical data, duration of illness and high disease activity to recruitment seem to negatively affects the answer to the first anti-TNF, suggesting that such parameters may have predictive value for the interruption of the drug. Disclosure of Interest: None Declared